2021
DOI: 10.1016/j.ophtha.2020.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Genotype Assay for Age-Related Macular Degeneration

Abstract: Purpose: To develop a genotype assay to assess associations with common and rare age-related macular degeneration (AMD) risk variants, to calculate an overall genetic risk score (GRS), and to identify potential misdiagnoses with inherited macular dystrophies that mimic AMD.Design: Case-control study.Participants: Individuals (n ¼ 4740) from 5 European cohorts. Methods: We designed single-molecule molecular inversion probes for target selection and used next generation sequencing to sequence 87 single nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 62 publications
5
69
0
Order By: Relevance
“…Each complement deficiency had been confirmed previously by genetic analysis, ELISA or radial immunodiffusion. Patients with AMD were screened by means of exome chip genotyping, 43 exome sequencing 44 and single‐molecule molecular inversion probes combined with next‐generation sequencing 45 . Additionally, we included three cases with a suspected but undiagnosed deficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Each complement deficiency had been confirmed previously by genetic analysis, ELISA or radial immunodiffusion. Patients with AMD were screened by means of exome chip genotyping, 43 exome sequencing 44 and single‐molecule molecular inversion probes combined with next‐generation sequencing 45 . Additionally, we included three cases with a suspected but undiagnosed deficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Most of these genetic risk factors have been confirmed in independent studies [70,72]. Although polymorphisms in the CFH and ARMS2/HTRA1 genes bear the highest single attributable risk scores for a single risk allele, additional genetic variants have been associated to AMD: in or near genes of the complement system (CFB, CFI, C2, C3); genes involved in ECM remodelling as Collagen Type VIII Alpha 1 Chain (COL8A1) and Tissue Inhibitor of Metalloproteinases 3 (TIMP3); genes involved in cholesterol metabolism as ATP-binding cassette transporter (ABCA1), Apolipoprotein E (APOE), Cholesteryl ester transfer protein (CETP), Lipase C, Hepatic Type (LIPC) and genes in less well-defined pathways, e.g., Rho GTPase Activating Protein 21 (ARHGAP21) and Beta 3-Glucosyltransferase (B3GALTL) [73]. The odds ratios of the representative SNPs in these genes typically fall into the range of 1.1-3.0, with a majority < 2; thus, each locus only has small to moderate contribution to the risk of the disease.…”
Section: Genetic Riskmentioning
confidence: 99%
“…Saskens et al identified mutations in CTNNA1 that cause butterfly-shaped pigment dystrophy (35). Very recently, a missense CTNNA1 mutation was identified in an age-related macular degeneration (AMD) patient (36). Furthermore, Alexander et al identified four mutations in CTNNA1 that cause macular pattern dystrophy (37).…”
Section: Introductionmentioning
confidence: 99%